2023
DOI: 10.3390/antibiotics12060946
|View full text |Cite
|
Sign up to set email alerts
|

Newer, Older, and Alternative Agents for the Eradication of Helicobacter pylori Infection: A Narrative Review

Abstract: Although discovered 40 years ago, Helicobacter pylori infection is still raising diagnostic and therapeutic problems today. The infection is currently managed based on statements in several guidelines, but implementing them in practice is a long process. Increasing antibiotic resistance and weak compliance of the patients limit the efficacy of eradication regimens, leaving much room for improvement. Third-generation proton pump inhibitors have added little to the results of the first two generations. Potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 107 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the pathogen dynamics with the microbiota of the gastrointestinal tract is highly complex, and eradication not only affects the gastrointestinal tract itself, but also its absence has been associated with dysbiosis and the emergence of a variety of systemic disorders, weight gain or loss, and susceptibility to allergic diseases such as asthma [43,[74][75][76][77][78][79]. In contrast, research over the years has demonstrated that eradicating H. pylori prior to the onset of precancerous histological changes can prevent the development of gastric cancer and dysbiosis can be managed with the integration to the antibiotic treatment of probiotics and other alternatives for microbiota modulation [80][81][82].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the pathogen dynamics with the microbiota of the gastrointestinal tract is highly complex, and eradication not only affects the gastrointestinal tract itself, but also its absence has been associated with dysbiosis and the emergence of a variety of systemic disorders, weight gain or loss, and susceptibility to allergic diseases such as asthma [43,[74][75][76][77][78][79]. In contrast, research over the years has demonstrated that eradicating H. pylori prior to the onset of precancerous histological changes can prevent the development of gastric cancer and dysbiosis can be managed with the integration to the antibiotic treatment of probiotics and other alternatives for microbiota modulation [80][81][82].…”
Section: Introductionmentioning
confidence: 99%